EFEKTIVITAS EKSTRAK BUAH DELIMA (Punica granatum) TERHADAP PENINGKATAN KADAR KALSIUM DALAM DARAH TIKUS PUTIH (Rattus norvegicus) - Indy Variety; Edrizal Edrizal; Eka Desnita (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
Pomegranate (Punica granatum) has been known to contain many active mineral ingredient such as iron, magnesium, potassium, zinc, phosphorus, including calcium. Calcium levels in this fruit are 10mg in every 100g it is almost equivalent to the levels of vitamin C in this fruit. The research aims to know the benefit and effectiveness of the extract pomegranate (Punica granatum) to increase calcium blood level of the white rats (Rattus n orvegicus). This study used an experimental laboratory method. The pomegranate extract (Punica granatum) made in the Kopertis Laboratory X. Dose of pomegranate (Punica granatum) made in pharmaceutical laboratory Andalas University, Padang are 2mg, 4 mg, 8mg, 16mg and negative control without giving any extract. The results of this study showed that the higher the dose given, also increase the calcium blood level. Compared with the negative control group, the pomegranate extract (Punica granatum) at doses of 2 mg, 4 mg, 8 mg resulted in calcium blood levels are lower than the negative control. While on the 16mg dose showed elevated the calcium blood levels compared to the negative control group. This shows that the smallest dose of pomegranate extract that is able to increase the calcium blood levels at 16mg dose. Anova test showed a significant result of the observation value (p<0.05) in increase a calcium blood levels of white rats (Rattus Norvegicus). Conclusion pomegranate extract (Punica Granatum) has an effect in increasing the calcium blood level but not significant.